DANUBE HYDROPOWER AND SOME RELATED PROBLEMS - Mircea POPOVICIU (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2013)
Danube has a length of 2912 km, a 6500 m3/s final discharge and a hydroelectric potential of 42 TWh, the recovery of which necessitate to build approximately 50 power plants. About 30% of this potential is found at the river sector making the Romanian-Serbian border. Two important hydroelectric and navigation systems “Iron Gates I” (1964-1971) and “Iron Gates II” (1977-1986) were built here. Paper analyzes the Danube from the point of view of the hydroelectric potential, compares the Iron Gates power plants with other similar achievements and examines the running behavior of this huge hydraulic equipment.